Country-Specific Factors and Capital Structure of the Oil and Gas Industry: A Review - Hamzah, Hana Halini; Maran Marimuthu, (Journal of Social Transformation and Regional Development, 2023)
Determinants of the capital structure still confusing among scholars. While numerous studies have been conducted, these are often limited to firm-specific factors such as profitability, asset tangibility, growth opportunities, liquidity, size, and non-debt tax shield. However, the literature clearly points out that there are important country-specific factors that determine capital structure decisions. Arguably, studies on determinants of capital structure focusing on country-specific factors for the oil and gas industry are still missing in the literature. As such, this study serves to review the determinants of capital structure with a specific focus on country-specific factors for the oil and gas industry. This study is to provide potential avenues for future researchers specifically in the oil and gas industry.